HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SMP NEGERI 2 SELAT PANJANG - Aseh, Trisni; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, problem in this study is the low student learning outcomes SMPN 2 Selat Panjang, because a lot of things, but the researchers looked at from the side of the students' motivation. This study aims to determine how much the relationship motivation toward learning outcomes of students in SMPN 2 Selat Panjang. This type of research is correlational. The population in this study were students of SMPN 2 Selat Panjang, amounting to 285. Samples were taken by purposive sampling, thus the number of samples of 53 people. Data analysis technique is using product moment correlation analysis. The results of this study were 1) There is a significant relationship between motivation toward learning outcomes boys, and this is evidenced from rhitung = 0.743> rtabel at α = 0.05 = 0.468. So in conclusion there is a significant relationship between motivation toward learning outcomes in SMPN 2 Selat Panjang. 2) There is a significant relationship between motivation toward student learning outcomes daughter, and this is evidenced from rhitung = 0.727> rtabel = 0.334. So in conclusion there is a significant relationship between motivation toward student learning outcomes daughter.Keywords : Motivation, Learning Outcomes